A Novel Mutation in the Membrane Frizzled-Related Protein Gene for Posterior Microphthalmia, Non-pigmented Retinitis Pigmentosa, Optic Nerve Drusen, and Retinoschisis in a Consanguineous Family - Ren, Xiang; Gao, Yunxia; Lin, Yu; Fu, Xiangyu; Xiao, Lirong; Wang, Xiaoyue; Zeng, Zhibing; Bao, Li; Yan, Naihong; Zhang, Ming; Tang, Li (Frontiers in Medicine, 2022)
Background: Microphthalmos (MCO) is a rare developmental defect characterized by small malformed eyes. Our study aimed to describe the clinical characteristics of posterior microphthalmos syndrome caused by a novel mutation in the MFRP gene in a Chinese patient. Methods: Complete ophthalmologic examinations were performed for the proband and proband’s family members. Whole exon sequencing (WES) and Sanger sequencing were used to identify the mutated genes, and bioinformatic analysis was undertaken to predict the effect of this variant. Result: Clinical analysis showed that the proband had reduced axial length (17.95 mm and 17.98 mm) with normal-size corneas and shallow anterior chamber depth. Fundus photography showed scatterred yellowish-white spots in the whole retina with cup-to-disc ratios of 0.95 in both eyes. Retinoschisis in the inner nuclear layer and reduced outer retina thickness were apparent on OCT examination, and optic nerve drusen showed increased autofluorescence in fundus autofluorescence (FAF). Perimeter examination displayed a tubular visual field for the right eye, and electroretinography (ERG) revealed a moderately reduced rod response combined with compromised cone response. Ocular examinations of the patient’s family members were unremarkable. WES revealed that the proband had homozygous mutations in c.55-1(IVS1) G>A in intron 1 for the MFRP gene. Both the proband’s parents and offspring were confirmed to be heterozygous by Sanger sequencing. Bioinformatic analysis showed this mutation was deleterious. Conclusions: Our study further broadens the mutation and phenotype spectrum of the MFRP gene in microphthalmia.